Perceived Parental Control, Self-Criticism, and Nonsuicidal Self-Injury Among Adolescents: Testing the Reciprocal Relationships by a Three-Wave Cross-Lag Model. Issue 3 (3rd July 2017) - You, Jianing; Jiang, Yongqiang; Zhang, Mingqin; Du, Chao; Lin, Min-Pei; Leung, Freedom
Abstract : This study examined the prospective and reciprocal relationships among perceived parental control, self-criticism, and nonsuicidal self-injury (NSSI). We also examined the mediating effect of self-criticism in the relationship between perceived parental control and NSSI. We aimed to find out whether perceived parental control and self-criticism acted as risk factors for NSSI, or consequences of NSSI, or both. A group of 3, 600 Chinese adolescents (mean age = 14.63 years, 56.6% female) completed questionnaires, with measures assessing NSSI, self-criticism, and parental control. A cross-lag model was used to test the reciprocal relationships among variables at 3 time points with 6-month intervals. Perceived parental control and self-criticism did not reliably predict later NSSI, but NSSI predicted later perceived parental control and self-criticism. Findings of this study emphasize the adverse effects of NSSI, and shed light on the intervention efforts of this behavior.